Assessment of the investment situation in the Republic of Adygeya economy using lean production tools - G. V. Karamushko; N. G. Maskova (Новые технологии, 2019)
The problems of the regional investment sector have been assessed in the article using lean production tools. Methods of solving problems using lean production tools include identifying and formulating the causes of problems (deviations), developing corrective and preventive measures and drawing up an action plan for their implementation. The following indicators of investment attractiveness of the region have been analyzed using Pareto diagram: factors limiting production growth of enterprises in the region; motives of investment activity of enterprises of the Republic of Adygeya; investment forms of enterprises of the Republic of Adygeya; sources of investments of enterprises of the Republic of Adygeya. Pareto diagram makes it possible to focus efforts and resources on the elimination of the most significant problems and effectively distribute the efforts to resolve these problems. Strategic orientation of the socio-economic development of the region to increase the investment attractiveness of the region and ensure the competitiveness of the Republic of Adygeya requires new approaches to the analysis of problems in this area. The use of lean production techniques in the assessment of the regional investment sphere will allow to form an organizational culture based on the principles of lean production, as well as to prevent the occurrence of many losses and reveal the reserves for improving the efficiency of its development.